2014
DOI: 10.1128/aac.00038-14
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Multidrug Efflux Pumps in the Antimicrobial Resistance Property of Clinical Multidrug-Resistant Isolates of Neisseria gonorrhoeae

Abstract: The contribution of drug efflux pumps in clinical isolates of Neisseria gonorrhoeae that express extensively drug-resistant or multidrug-resistant phenotypes has heretofore not been examined. Accordingly, we assessed the effect on antimicrobial resistance of loss of the three gonococcal efflux pumps associated with a known capacity to export antimicrobials (MtrC-MtrD-MtrE, MacA-MacB, and NorM) in such clinical isolates. We report that the MIC of several antimicrobials, including seven previously and currently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
91
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 36 publications
6
91
0
Order By: Relevance
“…The MtrCDE efflux pump influenced susceptibility to lefamulin, as reported for several antimicrobial classes (20). Further studies on the effect of the MtrCDE efflux pump on lefamulin activity and in vitro studies selecting for resistance to lefamulin, using subinhibitory lefamulin concentrations, detailing the resistance determinants in gonococci and investigating the fitness of selected resistant mutants would be valuable to predict the future emergence and transmission of lefamulin resistance.…”
mentioning
confidence: 81%
See 1 more Smart Citation
“…The MtrCDE efflux pump influenced susceptibility to lefamulin, as reported for several antimicrobial classes (20). Further studies on the effect of the MtrCDE efflux pump on lefamulin activity and in vitro studies selecting for resistance to lefamulin, using subinhibitory lefamulin concentrations, detailing the resistance determinants in gonococci and investigating the fitness of selected resistant mutants would be valuable to predict the future emergence and transmission of lefamulin resistance.…”
mentioning
confidence: 81%
“…The mtrD, macA, and norM genes, coding for (sub)components of the respective efflux pumps, were inactivated in WHO F, WHO O, WHO P, and WHO X (14), and one clinical strain with high-level azithromycin resistance (HLAziR; azithromycin MIC Ն256 g/ml), as previously described (20).…”
mentioning
confidence: 99%
“…Nevertheless, understanding of the effects on the MIC of ETX0914 by other mutations in the gyrB gene and possible mutations in gyrA, parC, parE, and porB (encoding the PorB porin) genes as well as overexpression of efflux pumps is mainly lacking. It has been shown that overexpression of several efflux pumps, particularly MtrCDE, significantly contributes to higher MICs of many antimicrobials (28). Accordingly, it would be exceedingly valuable to perform additional genetic studies examining induced or selected resistance mutations and the frequency of these in the antimicrobial targets and porB and mutations resulting in an overexpression of the MtrCDE efflux pump, particularly, but also additional efflux pumps.…”
Section: Discussionmentioning
confidence: 99%
“…Effective STI control will require the political will to prioritise and invest in new 150 rapid molecular methods for predicting AMR (for AMR surveillance but ideally also to inform individualized treatment), [190][191][192] rapid point of care tests for diagnosis of gonorrhoea (ideally with combined prediction of AMR); 190,191 ideal phylogenomics of gonococci and their AMR (also in non-cultured samples); 159,457,[459][460][461][462][463][464] and appropriate models for pharmacokinetics/ pharmacodynamics (urogenital and extragenital sites) and prediction of AMR induction/selection, evolution and biological fitness. -Data are for principal diagnosis, recorded using the ICD-9-CM from 1993-94 to 1997-98, and recording using the ICD-10-AM (Australian modification) from 1998-99.…”
mentioning
confidence: 99%